Variations in microbial community in a tropical dry deciduous forest across the season and topographical gradient assessed through signature fatty acid biomarkers. Issue 1 (17th November 2019) - Bhardwaj, Yashpal; Sharma, Mahaveer P.; Pandey, Jitendra; Dubey, Suresh K.
Abstract: Being pivotal to nutrient mobilization and conservation, microbial communities are indispensible for sustenance of forest ecosystem. The pattern and drivers of active soil microbial communities remain less explored in tropical dry deciduous forests. The present study was conducted during two annual cycles at three forest sites (hilltop, middle and hillbase) in the tropical dry deciduous forest of Vindhyan plateau, India. Chloroform fumigation‐extraction and phospholipid fatty acid analysis (PLFA) were used to investigate soil microbial biomass and microbial community, respectively. Our results showed significant ( p  < .05) topographical and seasonal shift in the soil microbial community wherein, microbial biomass and PLFA concentration (as total PLFA and specific biomarkers) were highest at hillbase site. The fungal PLFAs/bacterial PLFAs (F/B) and gram positive bacterial (G + )/gram negative bacterial (G − ) (G + /G − ) ratio also varied significantly with topography and season indicating specific changes in microbial communities. In general, bacteria dominated the overall scenario, and gram‐positive PLFAs biomarker dominated the total bacterial PLFAs. In the fungal counterpart, AM fungi showed prevalence. The soil organic carbon and nitrogen showed positive correlation with the microbial biomass, total bacterial PLFAs concentration and specific biomarker groups. The highest level of microbial biomass and PLFAs observed during summer indicated nutrients immobilization. The study has implications in understanding the microbial basis of nutrient turnover in the ecosystem perspective. Abstract : The present communication aimed to unravel the microbial biomass and community dynamics across season and topographical gradient of a tropical dry deciduous forest ecosystem in Vindhyan range, India.